Manual de referencia para la promocion de asociaciones de promotores y procesadores de yuca - Romanoff, S.A. (Fundación para el Desarrollo Agropecuario, 1989)
Basic information on how to train promoters is given as well as a series of procedures needed to successfully establish and develop new associations of cassava processors and promoters. Based on the experience acquired during the organization of the first associations in Manabi Province, Ecuador, 5 topics are covered, namely, (1) promoter-related information, indicating aspects important for fulfillment of his responsibilities and a glossary of work-specific terms; (2) details related to the formation and legalization of these associations; (3) responsibilities, statutes, and procedures of the Union of Associations of Cassava Producers and Processors (UAPPY) and the benefits offered to member- associations; (4) aspects related to the construction of a processing plant; and (5) operation of a processing plant (necessary equipment, quality control measures of the products, occupational safety, supervision). (CIAT)